RELIGIOUS ETHICS IN THE PUBLIC SPACE - Imam Safi'i (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2021)
This article is considered important based on the existence of religious-social phenomena that occur in the Ngapeh hamlet, Rejoagung village, Ngoro, Jombang district. In the Ngapeh hamlet community, there are three religions that live in harmony and harmony, namely Islam, Christianity and Hinduism. Islam is the majority religious group while Christians and Hindus are minority religious groups. Ngapeh Hamlet in Rejoagung Village can be said to be a unique area. Imagine a hamlet in the context of a small life but there is no domination of power from the majority of the people. The Muslim Ummah as the majority group is the prime mover in maintaining harmony between adherents of one religion and another. Christians and Hindus as minority groups do not experience discrimination from other ummah (Muslims). They are free to practice their beliefs and worship according to their respective religions. The research question to be answered in this study is how the pattern of religious interaction among the community in Rejoagung village, Ngoro sub-district, Jombang district, especially what occurs in Ngapah hamlet in implementing their diversity in public space as a form of a religious community ethics. To answer this question, in this study, Habermas' theory of communicative action is used which states that religious ethics is addressed by the public. In this paper it is found that the ethics of the religious community in public spaces are based on the role and function of religion itself. The function of religion in this paper is found three functions. First, religion as a force / dogma, religion as a sacred thing and religion as a spiritual act. Based on these three functions of religion, then based on Habermas's theory of discourse that in carrying out religious precepts in the Rejoagung village community, it is not only based on good things and is closed from political interests but religion must be a person's view of life and become a guide in ethics in the room. public.